Maternal mortality risk factor in pregnancy with heart disease at Dr. Soetomo General Hospital, Surabaya, Indonesia - Laili Muninggar; M Yusuf; Budi Prasetyo (Majalah Obstetri dan Ginekologi, 2019)
Objectives: This research want to identify some factors that increasing risk of maternal death in pregnant woman with heart disease.Materials and Methods: This study was a retrospective analytic study with cross sectional design, with total sampling 92 patient with heart disease in pregnancy at maternity room Dr. Soetomo hospital, Surabaya, during periode January until December 2017.Results: Prevalency of pregnancy with heart disease in dr. Soetomo hospital about 0,5% with mortality that caused by heart disease 14% from all maternal death. Factors that increase risk of maternal death are non adequate antenatal visit number (OR 1,7;CI 95%), delay of detecting heart disease (OR 2,5;CI 95%), complication such as severe pulmonal hypertension (OR 61,4;CI 95%), Eisenmenger syndrome (OR 2,9;CI 95%), Decompensatio Cordis Functional Class IV (OR 1,2;CI 95%), and Thrombo-embolism (OR 9;CI 95%).Conclusion: Mortality rate in pregnancy with heart disease is 14% of all maternal mortality. Risk of maternal death increased by non adequate antenatal visit and delay in heart disease detection, and also medical complications. Detection of heart disease since before pregnant with pre-conceptional councelling and a good managed multidisciplinary antenatal care supposed to decrease morbidity and mortality.